Makna dan Simbolisme dalam Novel Perburuan Karya Pramoedya Ananta Toer: Sebuah Kajian Sastra Postkolonial - Awtsaqubillah, Ahmad; Salwa, Balqis Meira; Zaskia, Hellen (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Baturaja, 2024)
Pramoedya Ananta Toer's novel Perburuan is one of the Indonesian literary works that raises the theme of history and postcolonialism. This novel depicts the life of Indonesian society during the Japanese occupation, with a focus on the struggle for independence experienced by the main character, Hardo, a leader of the rebellion against Japanese colonialism. The data collection technique used was a literature study, with the main data coming from Pramoedya Ananda Toer's novel Perburuan and relevant literature. In a historical context, Perburuan reflects the tension and resistance of colonial society against the colonizers, and shows the political and social realities during the transition to Indonesian independence. Through a postcolonial literary approach, this novel can be read as a form of criticism of colonial domination, while articulating the experiences of subalterns and marginalized voices in the official historical narrative. Pramoedya, with his narrative skills, successfully depicts the trauma, determination, and resistance of figures who strive to achieve freedom amidst uncertainty. Thus, Perburuan is not only a literary document about historical events, but also offers an alternative perspective that challenges the hegemony of colonial discourse, while enriching the study of postcolonial literature in Indonesia. The conclusion is that Pramoedya Ananta Toer's novel Perburuan makes an important contribution to Indonesian literature by depicting historical realities during the Japanese occupation while offering a postcolonial perspective that is critical of colonial hegemony. Through the character of Hardo, this novel displays the dynamics of the struggle and resistance of the Indonesian people in achieving independence, and articulates voices that have been marginalized by the official historical narrative. With a postcolonial literary approach, Perburuan is not only a literary witness to historical events, but also a medium for criticism of colonial domination and the affirmation of national identity. This novel enriches the study of postcolonial history and literature by offering a deep understanding of trauma, resilience, and socio-political dynamics in the pre-independence era of Indonesia. The purpose of writing this journal is 1. Identifying the Main Theme, analyzing the themes raised in the novel, such as the struggle against colonialism, betrayal, nationalism, and moral dilemmas. 2. Examining the Criticism of Colonial Hegemony, examining how this novel offers a postcolonial perspective by criticizing colonial domination and articulating the experiences of marginalized communities in historical narratives. 3. Examining the Dynamics of Figures and the Struggle for Independence, outlining the characterization of Hardo and the struggle, trauma, and resilience in it as symbols of resistance against the colonizers.